IMPLEMENTASI PROGRAM KEBIJAKAN KOTA LAYAK ANAK DALAM PERSPEKTIF KESEJAHTERAAN SOSIAL - Rika Halim Namma; Emei Dwinanarhati Setiamandani (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Child-friendly city is a development system of an administrative area which integrates commintments and resources of the governmet, society, and business worlds in the fulfillment of children’s rights in a planned, comprehensive and sustainable way. The purpose of this study was to determine the role of social service in the implementation of urban policy program eligiblechildren in Malang city. This type of research is a qualitative study using data gathered through observation, interviews, and documentation. Determination of inforamants by using purposive sampling. The data analysis was done through data reduction, data presentation, and verification. The result of research in accordance with the theory of policy implementation can be concluded that the social services of poor town has been carrying out its duties and functions in accordance with performance indicators of child-friendly cities. Supporting factor is the availability of adequate facilities for children, the fulfillment of children’s rights, empowerment of children as well as child protection and commitment in implementing urban policy program eligible children. Inhibiting factors include apparatus kirang resource support, poor communication goes well, and the participation of society which is still relatively low. Key Word: Implementation of Policies, Child-Friendly City, Social Welfare Abstrak: Kota Layak Anak (KLA) adalah sistem pembangunan suatu wilayah administrasi yang mengintegrasikan komitmen dan sumberdaya pemerintah, masyarakat dan dunia usaha yang terencana secara menyeluruh dan berkelanjutan dalam program dan kegiatan pemenuhan hak anak. Tujuan dari penelitian ini adalah untuk mengetahui peran Dinas Sosial dalam implementasi program kebijakan Kota layak Anak di Kota Malang. Jenis penelitian ini adalah kualitatif dengan menggunakan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Penentuan informan dilakukan dengan menggunakan purposive sampling. Analisis data dilakukan melalui reduksi data, penyajian data dan verifikasi. Dari hasil penelitian sesuai dengan teori implementasi kebijakan dapat disimpulkan bahwa Dinas Sosial Kota Malang sudah melaksanakan tugas dan fungsinya sesuai dengan indikator pelaksanaan Kota Layak Anak. Faktor pendukungnya adalah tersedianya fasilitas yang layak untuk anak, pemenuhan hak anak, pemberdayaan anak serta perlindungan anak dan tanggungjawab dalam melaksanakan program kebijakan Kota Layak Anak. Faktor penghambatnya meliputi sumberdaya aparatur yang kurang mendukung, komunikasi yang kurang berjalan dengan baik, serta partisipasi terhadap masyarakat yang masih tergolong rendah. Kata Kunci: Implementasi Kebijakan, Kota Layak Anak, Kesejahteraan Sosial